Experimental Study on Vibration Reduction of Helical Gears Based on GISFD - Zhu Gang; He Lidong; Yan Wei; Jia Xingyun (Jixie chuandong)
As an important part of mechanical transmission, gears have become one of the main sources of vibration and noise of mechanical equipment in the application process. In order to reduce and isolate the vibration of the helical gear system, a novel structure of G-type integral squeeze film damper (GISFD) is proposed, and the influence of GISFD on the vibration characteristics of the helical gear is explored. Based on GISFD, an open-type single-stage helical gear test bench is built, and the GISFD's influence experiment on the vibration characteristics of the helical gear system at different speeds is carried out. The experimental results show that GISFD has a good vibration reduction effect on helical gear shafts at different speeds. At 1,200 r/min, the vibration reduction of the main and secondary shaft of helical gear under GISFD can reach up to 59.61%. Meanwhile, GISFD can suppress the vibration of the helical gear meshing frequency and its second frequency, and the vibration reduction can reach up to 85.71%. GISFD also has a good vibration suppression effect on worn helical gears, and the vibration reduction in the horizontal direction of the driving shaft can reach 83.99% at 1 200 r/min.